Evaluation of the Clinical Effects of Abobotolinum Toxin A (Dysport) Injection in the Treatment of Neurogenic Lower Urinary Tract Dysfunction: Dysport injection in bladder and urethra - Sharifiaghdas, Farzaneh; Taheri, Maryam; Borumandnia, Nasrin; Sheikhi, Zhila (Urology Journal, 2021)
Purpose: Neurogenic lower urinary tract dysfunction (NLUTD) is one of the most challenging problems in urology. In recent years, Onabotulinum toxin A (Botox) is considered a second-line treatment in these patients. This study aimed to evaluate the clinical effects of Abobotolinum toxin A (Dysport) into the bladder and urethra. Materials and Methods: We classified our patients with NLUTD into three groups: neurogenic detrusor overactivity (group 1), detrusor sphincter dyssynergia (group 2), and patients with both symptoms (group 3). The severity of the patient’s symptoms was assessed using the Urinary Distress Inventory- Short form (UDI-6), urodynamic study, and post-void residual urine (PVR) at baseline. After injection of Dysport, the patients were evaluated by the change in UDI-6 score, PVR, and the patient’s general satisfaction. In group 1, 500-900 U diluted Dysport injected intra-vesical. If associated with detrusor sphincter dyssynergia (group 3), 100 U diluted Dysport injected peri-urethral. In group 2, only 100 U diluted Dysport injected peri-urethral. Results: Data from 52 women with NLUTD were analyzed. The mean age was 51.3 ± 21.6 years. The prevalence of detrusor overactivity and the value of Q max was more in group 1. However, the amount of PVR was more in groups 2 and 3. The overall success rate was acceptable in all three groups. In addition, there were significant improvements in UDI-6 parameters. Conclusion: Peri-urethral injection of Abobotolinum toxin A is effective and safe. However, the selection of the patients and the dose of toxin needs more studies.